Occurrence dataset of protected fungal species for the Red Data Book in Yugra Region, Western Siberia - Nina Filippova; Elena Zvyagina; Sergey Bolshakov; Stanislav Arefyev; Tatiana Bulyonkova; Ilya Filippov; Yury Rebriev; Anton Shiryaev; Iraida Stavishenko; Tatyana Svetasheva (Biodiversity Data Journal, 2025)
The data paper describes a dataset of occurrences of fungal species listed in the Red Data Book of Yugra Region (Western Siberia, Russia). The dataset is based on all digitised records of fungal occurrences in the region. The authors conducted an assessment of the conservation status of fungal species for the revised third edition of the Red Data Book of Yugra. The third edition of the Red Data Book of Yugra includes a total of 61 fungal species (excluding lichens). Of these, nine species are listed on the IUCN Red List and six are included in the Red Data Book of Russia. At the time of publication, the dataset comprises 1180 records of protected species, including human observations, preserved specimens and material citations from literature.The paper provides the first overview of the history of fungal conservation in Yugra (Khanty-Mansi Autonomous Okrug–Yugra, KhMAO-Yugra). For the first time, open-source data are used for the assessment of the occurrence of rare species and evaluation of their conservation status for the revised third edition of the Red Data Book of Yugra. An integrated occurrence dataset for the species included in the new edition of the Red Data Book is presented.